Nurturing Teacher Leadership: A Principal Strategy to Develop Teacher Leader in Madrasah - Sholihah, Hidayatus; Syukur, Fatah; Ismail, Ismail; Zaenurrosyid, Zaenurrosyid; Hussin, Zaharah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This research paper aims to interpret the experience of Islamic school (Madrasah) principals in nurturing leadership skills of Islamic Teaching (PAI) teachers to lead outside the classroom in three State Madrasah of Central Java, Indonesia. It was qualitative research with a Phenomenology approach, using in-depth interviews, observation, and documentation. Data was analyzed using the Miles and Huberman Model of analysis by applying three steps: data reduction, data display, and verification. The result shows that the principals of three Madrasah in Central Java have nurtured PAI teachers leaders by distributing the leadership roles, modeling persistently to lead the various programs, applying a democratic style of leadership, building teachers' intrinsic and extrinsic motivation to work, applying learning organization by facilitating teamwork, training and development program. Thus, PAI teacher leaders can be developed well in Madrasah, Central Java. This can lead to improving the Human resources teacher quality at Madrasah so that it can face the challenges in this 21st-century era.